A Conservative Method for Treating Severely Displaced Pediatric Mandibular Fractures: An Effective Alternative Technique - Sahand Samieirad; Saeedeh khajehahmadi; Elahe Tohidi; Meysam Pakravan (Mashhad University of Medical Sciences, 2016)
Pediatric mandibular fractures have been successfully managed in various ways. The use of a lingual splint is an option. This article presents a 4-year old boy who was treated by an alternative conservative method with a combination of an arch bar plus a lingual splint, circum-mandibular wiring and IMF for the reduction, stabilization and fixation of a severely displaced bilateral man‌dibular body fracture. This technique is a reliable, noninvasive procedure; it also limits the discomfort and morbidity associated with maxillomandibular fixation or open reduction and internal fixation in pediatric patients